Ihmiset ja kulttuuriperintö:Suomalaisten ja espanjalaisten opiskelijoiden välinen taidekasvatusprojekti - Ulkuniemi, Seija; Palacios, Alfredo (2017)
We present an integrative art exchange project between the University of Lapland (Finland) and Cardenal Cisneros University College (CUCC) (Spain). This project has been carried out over two academic years, 2013 and 2014, and there is an ongoing version of it for 2015. The main aim was to invite students to approach their cultural heritage, such as public art and architecture, from an artistic point of view. The students were asked also to exchange visual creations and ideas with the students of the partner university. The project presents effective integration within the discipline: it included art expression, knowledge in art, environmental education and media. In CUCC the project was also cross-curricular with contents of Didactics of Social Science. The principal task was to create a poster of the town (Rovaniemi or Alcalá de Henares), focusing on an element of artistic heritage. The students should also include a image of themselves and some essential words in the poster, and upload it in the joint blog on display. Partner university students wrote their interpretations about the poster, and finally the authors gave their explanation of the cultural meanings of the work. Students’ feedback was mainly positive, especially considering working internationally and in teams. With the help of critical feedback we improved the project, e.g. making it more structured. Some timing problems still remained. KEYWORDS: art education, heritage, public art, culture, integration, media, collaborative project, international, blog